Hemşirelik Öğrencilerinde İnternet Bağımlılığı, Fiziksel Aktivite, Uyku Düzeni ve Obezite Riski: Kesitsel Araştırma. - KARACAN, Yasemin; AKYÜZ, Feyza (Turkiye Klinikleri Journal of Nursing Sciences, 2026)
Objective: This study aimed to determine the level of internet addiction among nursing students and to examine its effects on physical activity, sleep patterns, body mass index, and obesity risk knowledge. Material and Methods: This cross-sectional study was conducted with 215 nursing students enrolled at a state university. Data were collected online using the personal information form, the Short Form of the Young Internet Addiction Test, the Single-Item Sleep Quality Scale, the International Physical Activity Questionnaire, and the Obesity Risk Knowledge Scale. Spearman correlation, simple linear regression, and multiple linear regression analyses were performed. Results: The participants had a mean age of 22.0±2.3 years, a mean body mass index of 21.9±3.5, and an average daily internet usage time of 5.0±2.0 hours. The mean internet addiction score was 27.74±8.51, indicating a low-to-moderate level of internet addiction. Internet addiction scores were a significant predictor only of body mass index (β=0.168; p=0.014). No statistically significant associations were found with sleep quality, physical activity level, or obesity risk knowledge. Internet addiction scores were higher among students who used the internet mainly for social media and entertainment, as well as those living in dormitories. Moreover, students using the internet for more than 7 hours daily had significantly higher addiction scores (p<0.01). Conclusion: The positive relationship between internet addiction and body mass index suggests that digital device use may negatively impact physical health. However, its associations with other health behaviors appear to be complex. Therefore, it is recommended that comprehensive educational programs be developed to raise awareness among nursing students regarding internet use and to promote healthy lifestyle behaviors.